SYBR® Green quantitative PCR for sex determination of bovine spermatozoa - Tan, Y. J. (2020)
Spermatozoa sexing technology in cattle breeding is being done by separation of X- and Y- chromosome bearing spermatozoa using flow-sorting technology. However, the sexing technique needed to be validated to ensure the accuracy of the technology. A technique to determine the sex of bovine spermatozoa using SYBR® Green real-time quantitative PCR (qPCR) was developed. Two sets of primers, ZFX and SRY were designed specifically to X- and Y- chromosome bovine genes respectively. Plasmid was inserted with ZFX and SRY gene fragment separately to create standard curves that ranged from 3.0 x 102 to 3.0 x 106 copies. The standards generated linear relationship with regression coefficient r2 = 0.984 for ZFX and r2 = 0.996 for SRY. Both standards of ZFX and SRY showed melting peak at temperature of 83 ºC and 85 ºC respectively. Real-time qPCR of bovine spermatozoa DNA samples and cloned plasmid ZFX and SRY genes for creating standard samples were performed simultaneously. The percentages of unsexed X- and Y- chromosome-bearing spermatozoa did not differ much from the 1:1 as reported in unsexed spermatozoa population. Therefore, the highly sensitive and fast method of real time PCR is a suitable technique for quantitating X- and Y- chromosome-bearing spermatozoa in semen samples.